Strategi Komunikasi Branding Impressive Probolinggo untuk Menarik Wisatawan - prasetyo, Bambang dwi (Universitas Brawijaya, 2020)
Many areas in Indonesia region still have social problems such as poverty, education, and health. The problem requires the local government to conduct communication strategies by increasing regional revenues through tourism. One of the regional efforts is to attract tourists visiting, through the city branding program. This article seeks to analyze the slogan Impressive Probolinggo is related to the tourism communication strategy of the Probolinggo City Government. The data was collected through interviews with City Government institutions, community leaders, and tourist visitors in 2018. The data was analyzed using an interactive qualitative method from Miles Huberman. The results showed that the slogan Impressive Probolinggo City became a city branding the Probolinggo City Government to attract tourists. The slogan is executed through a communication strategy that includes core and field communicators, worth of mouth-based messages, diverse media platforms, and involves community engagement. The government needs to improve socialization and design a more creative and innovative communication strategy so that the tourism potential in Probolinggo city develops sustainably.